Detection of a novel species A, DS‐1‐like, G4P[6] rotavirus strain from a Brazilian child with gastroenteritis. Issue 2 (30th August 2021) - Bandeira, Renato da Silva; Souto, Lizandra Caroline dos Santos; de Souza, Layse Costa; Linhares, Alexandre C.; Mascarenhas, Joana D'Arc Pereira
Abstract: Rotaviruses belonging to species A (RVA) remain among the most common causes of severe gastroenteritis in children aged <5 years, leading to substantial morbidity and mortality worldwide. Genome reassortment events between two human strains or human and animal strains represent one of the mechanisms which appear to generate the broad genetic variability of circulating. According to a nucleotide, sequence‐based classification system, RVA strains are currently classified into three genotype constellations including Wa‐like (genogroup I), DS‐1‐like (genogroup II), and AU‐like (genogroup III). The present study reports the detection of an unusual RVA G4P[6] strain (coded as strain HSE005), which might have originated from a natural reassortment event between human and animal RVA strains. Molecular characterization of this isolate showed that it belonged to genogroup II, genotype G4P[6]. In addition, two genes (VP3 and NSP4) of this strain denoted evidence of reassortment events involving strains of distinct zoonotic evolutionary origins. Therefore, we propose that a new G4P[6] strain was identified, highlighting a possible first zoonotic transmission including a reassortment event that involved the VP3 gene.